Integration of ontology and UML class-based modelling for knowledge representation / Rozita Kadar ... [et al.] - Kadar, Rozita; Syed Mohamad, Sharifah Mashita; Sumari, Putra; Abdul Rashid, Nur 'Aini (UiTM Cawangan Perlis, 2017)
Program comprehension is an important process carried out involving much effort in software maintenance process. A key challenge to developers in program comprehension process is to comprehend a source code. Nowadays, software systems have grown in size causing increase in developers' tasks to explore and understand millions of lines of source code. Meanwhile, source code is a crucial resource for developers to become familiar with a software system since some system documentations are often unavailable or outdated. However, there are problems exist in understanding source codes, which are tricky with different programming styles, and insufficient comments. Although many researchers have discussed different strategies and techniques to overcome program comprehension problem, only a shallow knowledge is obtained about the challenges in trying to understand a software system through reading source code. Therefore, this study attempts to overcome the problems in source code comprehension by suggesting a suitable comprehension technique. The proposed technique is based on using ontology approach for knowledge representation. This approach is able to easily explain the concept and relationship of program domain. Thus, the proposed work will create a better way for improving program comprehension.